BUYING DECISIONS FOR WARDAH COSMETICAL PRODUCTS IN TERMS OF PRODUCT QUALITY, BRAND IMAGE, AND CELEBRITY ENDORSEMENTS - Dea Fitriana Rahadewi; Bambang Mursito; Sudarwati Sudarwati (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to determine and analyze the effect of product quality on purchasing decisions for wardah cosmetic products, to determine and analyze the effect of brand image on purchasing decisions for wardah cosmetic products, to determine and analyze the influence of celebrity endorsers on purchasing decisions for wardah cosmetic products. This study uses a quantitative methodology. This research was conducted for four months. The population in this study are all consumers who buy wardah cosmetic products in Surakarta. The sample in this study consisted of 100 respondents. This study uses a non-probability sampling technique with purposive sampling. The results showed that product quality, brand image, and celebrity endorsements had a positive and significant impact on buying decisions for wardah cosmetic products in Surakarta. in the model of 35.7%, while the remaining variables of 64.3% are influenced by other factors that are not taken into account in this study. Keywords: Product Quality, Brand Image, Celebrity Endors, Buying Decision